Surface free energy and mechanical performance of LDPE/CBF composites containing toxic-metal free filler. (September 2017) - Yao, Zhitong; Heng, Jerry Y.Y.; Lanceros-Méndez, Senentxu; Pegoretti, Alessandro; Xia, Meisheng; Tang, Junhong; Wu, Weihong
Abstract: Heavy-metal contamination in children's toys is a widespread problem, and the international community has issued a series of safety standards to restrict and control the use of toxic metals in toys. In this work, a colored filler (CBF) was prepared using pearl oyster shell (POS) as the green raw material and azo dye as the colorant. Its surface properties were subsequently studied in comparison to those of POS powder using the inverse gas chromatography method. The dispersion surface free energy profiles for both CBF and POS showed that this component contributed the major part (>70%) to the total surface free energy. The CBF possessed lower polar surface free energy and was relatively more hydrophobic. It also showed a lower thermodynamic work of cohesion, allowing its better dispersion in a low density polyethylene (LDPE) matrix. Mechanical performance studies showed that adding CBF could significantly increase the tensile strength, elastic modulus, flexural strength and flexural modulus of LDPE composites. The absence of toxic metals coupled with excellent mechanical performance makes the CBF an ideal candidate as a filler for children's toys fabrication.